2003
DOI: 10.1136/adc.88.12.1058
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to the infant's last sleep environment in sudden infant death syndrome in the Republic of Ireland

Abstract: Aim: To identify risk factors for sudden infant death syndrome (SIDS) in the sleeping environment of Irish infants. Methods: A five year population based case-control study with parental interviews conducted for each case and three controls matched for age, place of birth, and last sleep period. A total of 203 SIDS cases and 622 control infants born 1994-98 were studied. Results: In a multivariate analysis, co-sleeping significantly increased the risk of SIDS both as a usual practice (adjusted OR 4.31; 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 33 publications
3
101
1
1
Order By: Relevance
“…Soft surfaces such as sofas have been found to be particularly hazardous for infants. (13,14,35) With increased awareness of the risk factors associated with bedsharing, it is important to try to understand why people in certain demographic categories bedshare more than others. For some families, the reason may be purely economic; they lack the funds to purchase a separate crib or bassinet for their child.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft surfaces such as sofas have been found to be particularly hazardous for infants. (13,14,35) With increased awareness of the risk factors associated with bedsharing, it is important to try to understand why people in certain demographic categories bedshare more than others. For some families, the reason may be purely economic; they lack the funds to purchase a separate crib or bassinet for their child.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…(4,5) As the rate of prone positioning has declined, other previously unrecognized risk factors for sudden unexplained infant death have emerged in recent epidemiologic studies. Despite the fact that bedsharing between an infant and adult facilitates breastfeeding and enhances parent-infant interactions, (6,7) this sleeping arrangement has been identified in epidemiologic studies as being hazardous in certain situations, particularly when one or both parents are smokers, (8)(9)(10)(11)(12) on excessively soft surfaces, such as waterbeds, sofas, and armchairs, (9,10,(13)(14)(15) or when the infant is less than 2-3 months of age. (9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers (13) and when bedsharing occurs for the entire night.…”
mentioning
confidence: 99%
“…We found 11 observational studies 5, 14, 18, 24, 25, 26, 27, 28, 29, 30, 31 that consistently showed a risk reduction of about 50% if the infant used a dummy (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…8,9,[15][16][17] However, this is the first large analysis comparing The finding of a greater association between sleeping on a sofa and surface sharing may be due in part to the inherent use of this type of furniture. Sofas and similar objects are often shared with others and are meant to be used during waking hours.…”
Section: Discussionmentioning
confidence: 99%